A Study of Methods of Sample Collection and Identification in Uroscopy - Ansari, Md. Khursid Alam; Taiyabi, Shabistan Fatma; Karim, Md. Shafat (International Journal of Medical Practitioners, 2023)
Uroscopy is the first documented laboratory test in medicine and is a fundamental diagnostic tool in the Unani system of medicine. Proper sample collection, handling, and identification are important to insure valid results in uroscopy.There are certain do’s and don’ts about the sampling mentioned in the text of the Unani medicine that should be followed. Generally, a urine sample is collected by the patient himself or herself, hence they must be educated to avoid contamination to ensure the purity of the sample. Despite this, there is a chance for error or malpractice hence collected samples should be identified for sufficiency and originality. There is a certain factor that can cause an erroneous result that must be avoided. Unani scholars have mentioned that sometimes patients brought other similar fluids or animal urine to test the competence of the physician or to mislead the diagnosis. To deal with such a situation differentiation of urine with other liquors should be made. The method of sample collection and identification for uroscopy are systematically summarized in this paper.
Keywords: Uroscopy; Unani medicine; Tafsareh; Quaroorah; Urine Analysis.